2021
DOI: 10.1002/pmrj.12607
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcomes and post‐discharge care sought by patients with COVID‐19 compared to matched controls after completing inpatient acute rehabilitation

Abstract: Introduction: A subset of patients with coronavirus disease 19 (COVID-19) can develop severe illness, resulting in significant functional and cognitive deficits that require acute inpatient rehabilitation. Guidelines following discharge from acute inpatient rehabilitation have not yet been established. This study seeks to establish outcomes of rehabilitation patients with COVID-19 and characterize their need for long-term care. Objective: To determine the functional outcomes and utilization of follow-up medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…In the manual search of gray literature and preprints, 18 potentially related papers were included. After reviewing the titles and abstracts of the articles, 157 peer-reviewed papers or preprinted manuscripts were reviewed and a total of 91 articles were entered into the present meta-analysis [ 8 , [14] , [15] , [16] , [17] , [18] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] ,…”
Section: Resultsmentioning
confidence: 99%
“…In the manual search of gray literature and preprints, 18 potentially related papers were included. After reviewing the titles and abstracts of the articles, 157 peer-reviewed papers or preprinted manuscripts were reviewed and a total of 91 articles were entered into the present meta-analysis [ 8 , [14] , [15] , [16] , [17] , [18] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] ,…”
Section: Resultsmentioning
confidence: 99%
“…Interventions identified as potentially preventing post Covid-19 condition included standard medication (14, 19, 36, 41, 47, 50, 56-59), traditional/ayurvedic medication (52, 53), stem cell therapy (49), rehabilitation or similar therapies (46, 51, 54), and screening and referrals (48, 55). We grouped interventions by timing, as those implemented during acute (symptom onset to 4 weeks) phase of Covid-19 with outcomes assessed at shorter (12-16 weeks) or longer (>16 weeks) follow-up duration post Covid-19; and interventions implemented during early post-acute (4-8 weeks) phase of Covid-19 with aforementioned shorter and longer follow-up time ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…We identified 3,595 records from searching databases and 186 records from other sources; 18 unique records, including 8 studies identified through the KQ1 search, met the eligibility criteria and were included (Figure 1; Tables 1 and S9) (14,19,36,41,(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59). Most of the studies originated from China (n=7); others were from USA (n=3), Italy (n=2), and one each from India, Iran, Belgium, Norway, Spain and Switzerland.…”
Section: Kq2: Preventive Interventionsmentioning
confidence: 99%
“…Olezene et al 23 (2021) evaluated the effectiveness of inpatient rehabilitation for 29 patients presenting after COVID-19 infection, showing statistically significant improvements in mobility, cognition, speech, swallowing, and balance by time of discharge. Jain et al 24 (2021) examined the outcomes of 64 patients admitted to acute inpatient rehabilitation after COVID-19. They also compared 18 patients admitted to inpatient rehabilitation after an admission for COVID-19 to 18 patients with the same impairment code and similar ages.…”
Section: Discussionmentioning
confidence: 99%
“…They found that individuals with COVID had similar functional outcomes, longer LOSs, and more cognitive symptoms compared with the comparison group. 24 …”
Section: Discussionmentioning
confidence: 99%